The theology of Handel's Messiah, Beethoven's Credo, and Verdi's Dies Irae how listening to sung theology leads to the contemplation of God - Greene, David B. (Lewiston : Edwin Mellen Press, 2011)
In pieces of music set to biblical or liturgical texts, the musical connections of one passage or one movement to one another. In a musical sense, these texts have a meaning and significance that can be and often distinct from the meanings achieved by syntactic relationships. Sometimes the syntactic meanings are lost in the musical repetitions and overlapping entries of many voices; in the case of texts for different movements, syntactic relations often simply do not exist. Consequently, the music does not merely parallel or illustrates the text's theological meaning or guide an affective resp.
Chapter One: Sacred Music, Theology, and Spirituality; Chapter Two: Hearing Mozart's Mass in C Minor: When Relating to Music is Relating to God; Chapter Three: "Et Resurrexit" from Bach's Mass in B Minor: Meditations on Discontinuous Continuity; Chapter Four: Messiaen, Quartet for the End of Time: New Visions of New Time.
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: Fine Arts; MUSIC / Instruction & Study / Voice; MUSIC / Lyrics; MUSIC / Printed Music / Vocal; Handel, George Frideric, -- 1685-1759.; Beethoven, Ludwig van, -- 1770-1827.; Verdi, Giuseppe, -- 1813-1901.; Music -- Religious aspects; Electronic books